The province of the memory: the “Historians debate 2.0” in Germany and the debate about the “saving” of the Bulgarian Jews - Decheva, Daniela (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2026)
The paper analyzes the “historians’ debate 2.0” in Germany and the debate about the rescue or deportation of the Bulgarian Jews using the term “province” and its derivatives in order to show distortions in both consolidated models of collective memory. Despite all the context-specific differences, both the German and the Bulgarian Holocaust controversy are extremely politically explosive. Both debates reflect historical factuality and complexity and at the same time take into account universalizing efforts in the politics of remembrance. They are therefore exemplary of the tension between globalization and the particularity of collective memory.